Power and data simultaneous transmission using double-clad fibers towards 6G - Letícia Carneiro de Souza; Felipe Batista Faro Pinto; Tomas Powell Villena Andrade; Arismar Cerqueira Sodré Junior (Scientific Reports)
Abstract To the best of our knowledge, this work represents the first report in the literature on the implementation of a radio- and power-over-fiber (RPoF) system utilizing double-clad fiber (DCF) aimed at the sixth generation of mobile communications networks (6G) operating in millimeter-waves (mm-waves). The deployed FiWi (fiber/wireless) system makes use of the DCF core and first cladding for simultaneously and optically transmitting data and power using the same fiber-optics link. For the first time, we demonstrate the simultaneous transmission of a broadband 26-GHz 5G New Radio (NR) signal in conjunction with 20 W of optical power through a 250-m DCF link. Such achievement represents a 150% reach enhancement, compared to the current commercial-available femtocells from the fourth and fifth generations of mobile communications networks (4G and 5G), which use Power-over-Ethernet (PoE) interfaces that typically provide 1 Gbps throughput limited to 100 m reach. The PoF key components of the remote antenna unit (RAU), such as the photodetector and RF amplifier, are optically powered by using PoF technology. We evaluate the PoF system efficiency and stability over extended periods and compare the analog RoF (A-RoF) system performance, by means of conventionally versus optically powered. Experimental results indicate the proposed RPoF system meets the 3rd Generation Partnership Project (3GPP) requirements, in terms of the root mean square error vector magnitude (EVMRMS), with no impairments. Overall, our FiWi system demonstrator provides a throughput of 1.6 Gbps using 16-quadrature amplitude modulation (QAM) over 5-m wireless transmission in the mm-waves band. The obtained experimental data highlight the feasibility of integrating optical and wireless technologies for supporting more reliable and scalable beyond 5G (B5G) and 6G systems.